DESAIN APLIKASI DIGITAL PADA PELAYANAN PERLAWATAN JEMAAT GKI DELIMA - Yudhi Windarto; Benisius; Wiryasaputra, Rita; Sevani, Nina; Putro, Endi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2023)
Digital transformation in church congregational visiting services is a challenge for GKI Delima where there are problems with data accuracy, coordination and reporting processes. The use of appropriate technology can be the best solution to overcome existing problems. The purpose of this community service program is to develop an Android-based application to improve the process of church congregational visiting services at GKI Delima. The stages of implementing this activity start from the planning, design-development and implementation stages. Application development refers to the RAD (Rapid Application Development) and using Android Studio. The results of the development of mobile apps for the GKI Delima congregation as part of the digital transformation process were able to improve the quality of the congregation's treatment process to become more effective and efficient. The scheduling and coordination process becomes faster and easier. Data is more accessible and faster in the process of updating data. The process of reporting and documenting the results of congregation visits has become easier, faster, safer, and paperless. The process of digital transformation in the congregation's visiting service at GKI Delima has had a positive impact on improving the quality of the congregation's visiting process to make it easier, faster and safer.